2000
DOI: 10.1128/jb.182.21.5962-5968.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Distal Tail Fiber Locus and Determination of the Receptor for Phage AR1, Which Specifically Infects Escherichia coli O157:H7

Abstract: Phage AR1 is similar to phage T4 in several essential genes but differs in host range. AR1 infects various isolates of Escherichia coli O157:H7 but does not infect K-12 strains that are commonly infected by T4. We report here the determinants that confer this infection specificity. In T-even phages, gp37 and gp38 are components of the tail fiber that are critical for phage-host interaction. The counterparts in AR1 may be similarly important and, therefore, were characterized. The AR1 gp37 has a sequence that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…OmpC has been reported to play a key role in virulence of Salmonella (Negm and Pistole 1999), and it also functions as the receptor for several phages. A major varied segment between residues176 and 226 has been reported to affect phage infectivity (Tommassen et al 1985;Mizuno et al 1987;Hikita et al 1989;Yu et al 2000). We found evidence of positive selection in residues 163, 202, and 203, located on loops 4 and 5, suggesting that the positive selection acting on ompC is selection to avoid phage binding, but selection to enhance OmpC's function as a virulence factor may also be important.…”
Section: Beta Barrel Porinsmentioning
confidence: 61%
“…OmpC has been reported to play a key role in virulence of Salmonella (Negm and Pistole 1999), and it also functions as the receptor for several phages. A major varied segment between residues176 and 226 has been reported to affect phage infectivity (Tommassen et al 1985;Mizuno et al 1987;Hikita et al 1989;Yu et al 2000). We found evidence of positive selection in residues 163, 202, and 203, located on loops 4 and 5, suggesting that the positive selection acting on ompC is selection to avoid phage binding, but selection to enhance OmpC's function as a virulence factor may also be important.…”
Section: Beta Barrel Porinsmentioning
confidence: 61%
“…In previous studies, partial sequences of AR1 showed a high degree of similarity to the corresponding sequences of T4 phage (17,37,89,90). In this study, we determined the complete genome sequence of AR1 (167,435 bp).…”
Section: Resultsmentioning
confidence: 99%
“…Host range receptor assays (17) showed that AR1 uses the R1, R3, and R4 core oligosaccharide (OS) types of lipopolysaccharide (LPS), but not the R2 or K-12 type, as cellular receptors (17). A previous study suggested that the putative AR1 gp37 receptor recognition protein may recognize and bind to the OmpC receptor because an E. coli O157:H7 OmpC disruption mutation rendered the cell resistant to AR1 infection (90). Similar to the case with T4 and other T4-like phages, restric-tion enzyme digestion experiments suggested that the AR1 genome is highly modified to protect it from restriction enzyme digestion by the host defense system (89).…”
mentioning
confidence: 99%
“…Only a few phages appear to have evolved by mutation maintaining the same structural framework. Residues 359-524 of T7 gp17 (encompassing all but the final 29 residues of our structure) have been classified in Pfam domain gp37_C, which includes a subset of the highly diverged Cterminal regions of the gp37-type tail-fiber proteins of T4-like phages, the subset found in phages AR1 and Ac3 (30). Thus, amino acid sequence comparisons suggest that the tapered triangular pyramid and part of the tip structure of T7 tail fibers may be structural building blocks used in fibers of phages of the Myoviridae as well as the Podoviridae family.…”
Section: Discussionmentioning
confidence: 99%